Pengaruh Kualitas Pelayanan dan Pengalaman Pasien terhadap Citra Merek dan Implikasinya pada Kepuasan Pasien - Humami, Anung; Basrowi, Basrowi; Khairuman, Khairuman (Jurnal Ecogen, 2024)
Based on preliminary data, this study indicates that there has been a decline in the number of outpatients in 2023.  The aim of this research is to investigate, using brand image as an intervening variable, the effects of patient experience and service quality on patient satisfaction.  This kind of research uses a causality design and is quantitative. The patients in question are outpatients.  Using a formula that increases the number of indicators by five observations, the non-probability sampling procedure yields 275 samples, or responders.  A questionnaire is used as the data gathering tool, while PLS-SEM and the three box method analysis are used as the data analysis techniques.  The analysis's findings demonstrate that while brand image influences patient satisfaction, patient experience influences brand image, and service quality influences patient satisfaction, brand image influences patient satisfaction.  While brand image can influence the association between patient experience and satisfaction, it cannot influence the relationship between service quality and patient contentment.